Bralna kultura s psihološke in z vzgojno-izobraževalne perspektive - Pečjak, Sonja (Revija za elementarno izobraževanje, 2021)
The article discusses reading culture and reading as a value in Slovenia, with theoretical considerations supported by empirical results of foreign and domestic psychological and educational studies on reading culture. In this paper we try to answer the questions of what reading culture is and what its elements are, when reading can become a value and what the obstacles are in the development of reading culture from the psychological perspective. We answer these questions from the perspective of the family and school environment and suggest some ways of dealing with these obstacles, especially from the perspective of the role of the family and the school or teachers, as pointed out by the National Strategy for the Development of Reading Literacy.
Keywords: branje; družinsko okolje; education; educational psychology; home environment; pedagoška psihologija; reading; schools; šola; vzgoja in izobraževanje